Protein-Ligand Binding as a Tool to Identify Antiviral Drugs. - (:unkn) unknown (My University, 2021)
Viruses are the most abundant biological entities on the planet. A virus is a collection of essential genetic material encapsulated in a protein coat that is incapable of replicating without a host. A virus must inject its genetic material into a suitable host cell to utilize host machinery to replicate. During the process of replication, a virus hijacks cellular functions, avoids or inhibits host antiviral defenses, and sometimes causes disease in the host organism. One effective way to fight viral infection is to identify molecules that inhibit the function of essential viral proteins. The studies described in this dissertation focus on identifying such molecules. Even if such molecules are not developed into drugs, they could be useful as molecular probes to study the biological role of these viral protein targets. The two targets studied here were helicases, which bind ATP and nucleic acids, and macrodomains, which bind ADP-ribose. The proteins were isolated from either the hepatitis C virus (HCV) or SARS-CoV-2, the virus that causes COVID-19.To facilitate similar drug discovery screens with helicases, two assays were designed to monitor DNA and ATP binding to viral helicases. DNA binding was monitored with Förster resonance energy transfer (FRET), fluorescently labeled HCV helicase, and fluorescently labeled oligonucleotides. Factors effecting binding were examined, such as the length of the duplex, the length of a single-stranded overhang, and whether the overhang had a 5’ or 3’ end. Less FRET was observed with longer length duplex, and longer length single-stranded overhang. To monitor the interaction of ATP and a helicase, the steady state rates of ATP hydrolysis catalyzed by nsp13, a helicase from SARS-CoV-2, were measured. Based on the rates of helicase-catalyzed ATP hydrolysis, the catalytic rate constant, Kcat, was calculated. To monitor the binding of DNA (or RNA) to nsp13, rates of ATP hydrolysis were examined in the presence and absence of various oligonucleotides. Oligonucleotides with a length of 18–20 base pairs stimulated the helicase-catalyzed ATP hydrolysis by increasing rates of ATP hydrolysis, but poly(U) and other longer polynucleotides had no impact. In the similar binding studies, Isothermal Titration Calorimetry (ITC) was used to show ADP-ribose binding to the macrodomain (Mac1) of SARS-CoV-2 was enthalpy (ΔH) driven. The interactions between Mac1 and nucleotides similar to ADP-ribose were also investigated with ITC. However, their interaction was not similar to that of ADP-ribose. The next step was to screen a library of 2,500 compounds in search of potential antiviral candidates or compounds that would bind to Mac1, blocking its interaction with ADP-ribose using Differential Scanning Fluorimetry (DSF). Compound effects were confirmed with DSF and ITC, and imatinib methane sulfonate was shown to bind Mac1 in a similar manner to that of ADP-ribose. In this dissertation, multiple methods were employed to examine the interaction between protein and small molecule, protein-DNA, and protein-RNA. Even though not all methods and techniques employed resulted in identifying potential antivirals, these are the initial studies required to move forward before proceeding to identify potential antivirals.
Keywords: Coronavirus; COVID-19; Hepatitis C virus; Isothermal Titration Calorimetry; SARS-CoV; SARS-CoV-2